(untitled) (Journal of Medicine, 2009)
Primary hypothyroidism is a common clinical condition. Ascites caused by hypothyroidism is rare. So its diagnosis is often delayed and patients frequently receive unnecessary procedures such as liver biopsies and exploratory laparotomies. We report a male person of 58 years with hypothyroidism with ascites who responded well with thyroid hormone replacement therapy with complete resolution of ascites. Analyses of ascites from patients in this condition usually shows exudative ascites with high protein (>2.5 g/dL) and SAAG < 1.1 gm/dl. High index of suspicion is required to reach at such diagnosis. Though it is a rare but prognosis is excellent with replacement therapy. Key words: Ascites, Hypothyroidism. doi: 10.3329/jom.v10i2.2828 J MEDICINE 2009; 10 : 121-123